Female changes : the violation and violence of women in Ovid's Metamorphoses - Champanis, Leigh Alexandra (Rhodes University, Faculty of Humanities, School of Languages, 2013)
Ovid's interest in women and their lives is apparent throughout his texts, but is especially so in the Metamorphoses. This study analyses the violation and violence of women in the Roman poet's epic and sets out to uncover the governing social mores and values that perhaps shaped the representations of women in the text. It examines how Ovid's narratives may betray his values and attitudes and those of his audience as well as looking at the various ways that the poet and his rape episodes have been read. After surveying the literature on rape in Ovid's Metamorphoses, Ars Amatoria and the Fasti, a brief historical context for the Metamorphoses is provided; women's lives in Rome, the rape laws that existed during this time, as well as Roman sexuality are then examined. After this, a close textual analysis of different rape episodes in the Metamorphoses is presented, including the episodes of nymphs as victims, the silencing of rape victims and sexually 'aggressive' women, in order to reveal and examine the patterns that emerge. While Ovid's intentions and attitudes towards women, as they are found in the Metamorphoses, have been read by some as sympathetic, by others as misogynistic and still others as more neutral, it is concluded that, although there is space for various readings, as a poet, Ovid was 'opportunistic' in his choice of materia and, above all, he wished to stimulate and delight his audience. While his personal values may not necessarily be reflected in his works and his readers may never know the 'true' intentions behind the poem, the Metamorphoses does hold up a mirror to the negative treatment of women and exposes the gender inequalities that existed during Ovid's time. As a poet, however, Ovid's conceived role is to entertain his audience and despite his somewhat problematic treatment of women and rape victims, he does just that.
Keywords: Ovid, 43 B.C. - 17 or 18 A.D. -- Criticism and interpretation; Ovid, 43 B.C. - 17 or 18 A.D. -- Metamorphoses; Rape; Women -- Violence against; Violence in women